Construções de reticulados via corpos de números - Nogueira, Ana Flavia Cesario Machado Alckmin [UNIFESP] (2020)
In this work we study of the theoretical basis that grounding the theory of algebraic lattices and we present some constructions of the E8 lattice with emphasis on the construction presents in the paper A new number field construction of the lattice E8. For this purpose, it were studied concepts of algebraic number theory, Galois theory and lattice theory.